Factors influencing civil engineering project performance - Wan Norizan Wan Ismail,; Hamimah Adnan,; Natasha Khalil, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Civil engineering projects trigger the economic growth by providing infrastructure facilities and job opportunities as well as attracting the attention of foreign investments. Due to their significant contributions towards the nation growth, the performance of civil engineering projects has become the upmost concern by the government. Unfortunately, many civil engineering projects in Malaysia are dominantly associated with unsatisfactory performance in terms of cost, time and quality of the delivered products. Therefore, this paper aims to identify the underlying causes which lead to unsatisfactory performance by determining the factors that affect civil engineering projects. The objective of this paper is to assess the factors i.e the civil engineering project characteristics and the quality of Standard Form of Contract (SFoC) adopted and the contractual behaviour of key participants of civil engineering project which affect the performance. The perceptions of consultant engineers and contractors were compared relatively to a list of these factors derived from the review of literature in construction of project performance. Questionnaires survey were conducted to undertake the research. 214 feedbacks received out of 500 questionnaires distributed to the G7 contractors registered under Construction Industry Development Board (CIDB) and consultant engineer registered under Board of Engineers Malaysia (BEM). The data was statistically analysed using SPSS 21 and descriptive analysis was conducted to determine the rank of factors. It is found that the civil engineering project characteristics namely project complexity, ground uncertainty, ease of site access and design completion before construction starts perceived to have high influence of project performance. Meanwhile, the quality of SFoC factors i.e completeness and clarity and contractual behaviours of key participants’ factors i.e delay in making payment and communication skill between engineer and contractor were also ranked as the high-influence factor influencing civil engineering project performance. Thus, as a proactive measure, these factors are paramount to be put more concern in monitoring the performance of civil engineering projects in Malaysia.